Faith-Based Mental Health Promotion in Muslim Communities: The Role of Islamic Education and Spiritual Practices - Elfattah, Hagar Yehia Abd (Yayasan Sinergi Kawula Muda, 2025)
Islamic education has emerged as a critical avenue for supporting mental health through its integration of spiritual values and character formation. This study employed a narrative review method to synthesize findings from scholarly literature on the effectiveness of Islamic educational curricula and spiritual interventions in enhancing students' psychological resilience. Data sources included peer-reviewed articles exploring the impact of spiritual practices, such as dhikr and expressive writing, within formal Islamic schooling and pesantren contexts. Findings reveal that Islamic education frameworks—when designed holistically—contribute significantly to reducing stress, anxiety, and depression symptoms among students. Interventions rooted in Islamic spirituality not only foster emotional well-being but also build internal coping mechanisms, especially when supported by community and family involvement. However, systemic limitations—such as a lack of teacher training, rigid curricula, and policy fragmentation—diminish the scalability of such programs. This review advocates for the integration of faith-based mental health interventions into national education and health policies. It recommends increased investment in teacher training, the development of interdisciplinary teams, and the use of digital platforms for broader outreach. Future research should investigate long-term outcomes and adapt models for minority and urban settings. The synthesis confirms that Islamic education provides a culturally embedded and sustainable model for mental health promotion in Muslim-majority contexts